The Impact of Dental Hypersensitivity on the Patients Quality of Life. A Questionnaire-Based study - Mihaela Stoica, Alexandra; Monea, Monica; Dako, Timea; Elena Stoica, Oana; Beresescu, Liana (European Scientific Journal, ESJ, 2022)
Introduction: Dentinal hypersensitivity is a pathological condition with an increased incidence among patients of various ages, affecting their well-being and with a common response for a wide range of treatment strategies. The study aimed to assess the impact of teeth hypersensitivity on the quality of life, daily activities, and on the emotional status of the patients affected by it. Method: We conducted an anonymous survey on a group of 200 patients with ages 20 and 65 years old, using a questionnaire that included 23 questions. The results were collected and statistically analyzed using the chi-square test. Results: Out of all the patients who answered our questionnaires, 51 percent have ages between 20-25 years, 26 percent between 26-35 years, 12 percent between 36-45 years, respectively 11 percent represent patients older than 46 years. 81 percent of patients are female, and 19 percent are male. In 65 percent, the onset of dental hypersensitivity sensations is caused by the consumption of ice cream, affecting the patients‘ lifestyle negatively. According to the study, 36 percent of patients give up on certain foods/drinks that led to the appearance of dentinal hypersensitivity sensations. Forty-one correspondents felt compelled to give up consuming cold food, and carbonated and sour drinks. Conclusions: Dentin hypersensitivity is represented by the appearance of an uncomfortable sensation due to dentin being exposed to the exterior environment, a sensation that can range from mild irritation to severe pain and can reduce the quality of mastication and oral hygiene.